Analysis and simulation of badminton shuttlecock flight through parameter identification of a slow-speed serve shot - Lin, C. S. H.; Chua, C. K.; Yeo, J. H. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2015)
An experimental method to obtain flight parameters from the trajectory of a badminton shuttlecock is described. This methodology is able to identify the aerodynamic parameters and simulate the various flight trajectories of a badminton shuttlecock. Two shuttlecocks were evaluated - a feather shuttlecock and a prototype synthetic shuttlecock. The four flight modes of the feather shuttlecocks were captured experimentally through an array of high-speed cameras. Flight parameters were identified from the serve shot of the feather shuttlecock to simulate the net shot, smash and clear flight path. The simulated trajectories were evaluated against the experimental trajectories to validate the proposed methodology. While slight deviation was observed, the simulated trajectories follow closely to the experimental result. Serve-shot trajectory data were then recorded for the prototype synthetic shuttlecock for parameter identification and trajectory simulation. The results showed significant variation in the clear and smash shots due to insufficient drag on the prototype. The net shot showed good agreement with the feather shuttlecock. This phenomenon is discussed. The work conducted is useful for evaluating early-stage prototypes which may not be sufficiently durable to sustain a clear-shot or smash-shot test.